Spontaneous healing how to discover and enhance your body's natural ability to maintain and heal itself - Weil, Andrew (Alfred A. Knopf, 1995)
In this revolutionary book, Dr. Andrew Weil, one of the most authoritative, articulate, and important voices in the field of health and healing, makes clear the reality of spontaneous healing. He illuminates the mechanisms and processes of the body's healing system, delineates the ways in which an individual can optimize the functioning of his or her own system, and outlines the alternative medicines and treatments available to aid the healing system, not only in the remission of life-threatening diseases but also in response to everyday illnesses and in day-to-day upkeep of basic health. In clear, concise language, Dr. Weil explains how the healing system operates, its interactions with the mind, its biological organization, its systems of self-diagnosis, self-repair, and regeneration.